1750 Mass. Acts 544 - (:unkn) unknown (My University, 1750)
An Act for Preventing and Suppressing of Riots, Routs and Unlawful Assemblies, ch. 17, § 1: Prohibited the carrying of a club or other weapon while unlawfully, riotously, or tumultuously assembling. Punishable by seizing the weapon and a hearing before the court.
Keywords: CARRY - INTENT TO COMMIT CRIME